A coumarin-based fluorescent probe for sensitive monitoring H2O2 in water and living cells. (12th January 2023) - Li, Yuanyuan; Ren, Lidan; Gao, Tingting; Chen, Tong; Han, Juan; Wang, Yun
Graphical abstract: Highlights: The fluorescence probe can quantitatively detect hydrogen peroxide with a high detection sensitivity (detection limit 118.2 nM). The probe has good biocompatibility that can be used to detect exogenous and endogenous hydrogen peroxide in cells. The fluorescent probe has the advantages of simple preparation process and low cost. Abstract: By introducing boronate esters as a recognition unit, a fluorescent probe (Probe 1) was developed for the qualitative and quantitative determination of hydrogen peroxide. Absorbance spectra and fluorescence emission spectra of Probe 1 and the reaction product were studied. It was found that maximum absorbance peak changed from 321 nm to 372 nm and an emission peak centered at 451 nm appeared. The fluorescence intensity at 451 nm enhanced with the linear increase of the H2 O2 concentration (0–180 µM) and the detection limit was calculated to be 118.2 nM. Even in the presence of various ions, the fluorescence intensity remained relatively unchanged. Moreover, Probe 1 was further used to image macrophage RAW264.7 and colon cancer cell SW480 because it worked excellently under leaning alkalinity condition, which indicated the good cell-membrane permeability of Probe 1 and its potential ability to detect the exogenous and endogenous H2 O2 in living organisms.